State Loss Settlement Policies in the Bank Indonesia Liquidity Assistance Case - Hasbullah Hasbullah; Huala Adolf; Sigid Suseno (Lembaga Contrarius Indonesia, 2026)
Despite extensive policy and legal responses to the Bank Indonesia Liquidity Assistance (BLBI) program, existing scholarship has predominantly concentrated on macroeconomic stabilization measures, institutional accountability, and post-crisis regulatory reform. However, these studies have paid limited attention to the mechanisms of fund misappropriation at the implementation level and to the normative gaps in supervisory and legal frameworks that enabled state financial losses. This study examines legal and structural causes of ineffective BLBI loss recovery, evaluates comparative crisis resolution frameworks, and formulates an ideal legal model ensuring certainty, asset recovery, and public interest protection. The research adopts a normative legal methodology employing legislative, conceptual, and case-based approaches. The findings demonstrate that, first, the BLBI dispute exposes systemic deficiencies in Indonesia’s law enforcement system, particularly weaknesses in substantive legal norms, institutional capacity, and legal culture, which collectively prolonged dispute resolution and imposed a substantial fiscal burden on the state. Second, comparative analysis shows that countries such as Thailand and South Korea effectively managed banking liquidity through independent, coherent, and responsive legal frameworks, while Indonesia continues to encounter structural constraints that impede effective BLBI settlement. Third, effective recovery of state losses requires the reconstruction of an integrated legal framework that prioritizes legal certainty, asset-focused enforcement, institutional independence, legal culture reform, and clearly defined national procedures, supported by robust inter-agency coordination and international cooperation to prevent the recurrence of structural impediments.